2016
DOI: 10.1007/s10509-016-2692-5
|View full text |Cite
|
Sign up to set email alerts
|

R-mode constraints from neutron star equation of state

Abstract: The gravitational radiation has been proposed a long time before, as an explanation for the observed relatively low spin frequencies of young neutron stars and of accreting neutron stars in low-mass X-ray binaries as well. In the present work we studied the effects of the neutron star equation of state on the r-mode instability window of rotating neutron stars. Firstly, we employed a set of analytical solution of the Tolman-Oppemheimer-Volkoff equations with special emphasis on the Tolman VII solution. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 72 publications
1
20
0
1
Order By: Relevance
“…The bulk viscosity in equation ( 6) should be computed for the modified URCA process, but here we have used the approximate expression used in Refs. [35,25,65], given by…”
Section: Dissipative Time Scales and Stability Of The R-modesmentioning
confidence: 99%
“…The bulk viscosity in equation ( 6) should be computed for the modified URCA process, but here we have used the approximate expression used in Refs. [35,25,65], given by…”
Section: Dissipative Time Scales and Stability Of The R-modesmentioning
confidence: 99%
“…The Nariai IV solution [17,18,19] is the most complicated and less known, compared to the previous ones. This solution has been employed in neutron stars studies [22,25]. However, the stability of this solution, according to our knowledge, is examined for a first time in the literature.…”
Section: Nariai IV Solutionmentioning
confidence: 99%
“…The r-mode instability (Andersson 1998;Friedman & Morsink 1998;Andersson & Kokkotas 1998;Ho & Lai 2000) can trigger the exponential growth of gravitational wave (GW) emission in rapidly rotating neutron stars through the Chandrasekhar-Friedman-Schutz mechanism (Chandrasekhar 1970;Friedman & Schutz 1978) if the GW growth rate is faster than its damping rate. Over the past two decades, significant efforts have been devoted to better understanding the r-mode instability and its damping mechanisms with many interesting findings (see, e.g., Madsen 2000;Yang et al 2011;Wen et al 2012;Vidaña 2012;Haskell et al 2012;Alford & Schwenzer 2014a,b;Idrisy et al 2015;Moustakidis 2015;Dai et al 2016;Papazoglou & Moustakidis 2016;Ofengeim et al 2019;Wang et al 2019;Krüger & Kokkotas 2020). In particular, it was found that the r-mode instability window (a region in the spin frequency versus temperature plane) in which the r-mode is unstable depends sensitively on the EOS of neutron-rich matter, especially its symmetry energy term which encodes the information about the energy cost to make nuclear matter more neutron-rich.…”
Section: Introductionmentioning
confidence: 99%